Challenges faced by anesthesiologists during the cesarean section of COVID-19 patients – An observational study - Lakhanapal, Mahima; Kumar, Ritesh; Amit Kumar; Isha Yadav (Asian Journal of Medical Sciences, 2022)
Background: The health-care system has encountered exceptional circumstances, experiencing unique challenges, and manifesting as acute challenges in health-care services due to the spread of COVID-19. Aims and Objectives: The present study aimed to report the difficulties faced by the anesthetists while performing a cesarean section under the subarachnoid block (SAB) in COVID-19 patients at a dedicated COVID Level 3 hospital. Materials and Methods: Twenty healthy anesthetists (six consultants and 14 postgraduate) aged 20–40 years performed 60 elective or emergency cesarean sections of known COVID-19-positive gravida patients aged 20–35 years with no comorbidity and no spine abnormality under the SAB. Anesthetist;s responses to the challenges faced while performing procedures wearing the Level 3 personal protective equipment were recorded using a pre-structure self-administered questionnaire. To quantify the intensity of these problems, all the physical and psychological difficulties were graded as mild, moderate, and severe. Results: In the present study, 75% experienced moderate-to-severe sweating, and 60% experienced moderate-to-severe headaches. A total of 45% experienced moderate-to-severe breathlessness. Though there was little difficulty in communication among doctors and staff, almost 75% of anesthetists faced it. The fear of contracting the disease and spreading it to the family members was expressed by 75–80% of anesthetists. Conclusion: The present scenario has increased physical stress and other psychological problems among health workers. Therefore, hospital support with regular psychological counseling sessions is needed for healthcare workers to cope with the current situation.